Hubungan Polimorfisme Gen Laktoferin dengan Kualitas Susu pada Sapi Perah Friesian-Holstein - Elmy Mariana (Jurnal Agripet, 2011)
Association of Lactoferrin Polymhorphism on Milk Yield and Milk Quality in Holstein-Friesian Dairy CowsABSTRACT. The purposes of this study were to identify the polymorphism of the lactoferrin gene and the association of genetic variants of the lactoferrin gene on milk quality in Holstein-Friesian (HF) cows. The study was conducted on 194 heads of HF lactating cows coming from semi intensive of small dairy farmers in two villages of the KPSBU Lembang, Lembang district. Investigation on variant genotypes of the lactoferrin gene used PCR-RFLP method. Genotyping of the lactoferrin gene with EcoRI restriction enzyme produced two genotypes, i.e. AA (65%) and AB (35%) genotypes. Both the AA and AB genotypes had inconsistency in controlling component of the milk quality. Further, the AB lactoferrin cows had a higher frequency in the classification of low somatic cells count (0.75), while the AA cows were at a higher frequency in the classification of high somatic cells count (0.60). It was concluded that there is no strong relationship between intron 6 lactoferrin gene with milk quality parameters. Further, the AB genotype of the lactoferrin gene had a consistency in producing lower somatic cells count compared to the AA genotype.